If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3y(4x + 24) = -2 Reorder the terms: 2x + -3y(24 + 4x) = -2 2x + (24 * -3y + 4x * -3y) = -2 Reorder the terms: 2x + (-12xy + -72y) = -2 2x + (-12xy + -72y) = -2 Solving 2x + -12xy + -72y = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '72y' to each side of the equation. 2x + -12xy + -72y + 72y = -2 + 72y Combine like terms: -72y + 72y = 0 2x + -12xy + 0 = -2 + 72y 2x + -12xy = -2 + 72y Reorder the terms: 2 + 2x + -12xy + -72y = -2 + 72y + 2 + -72y Reorder the terms: 2 + 2x + -12xy + -72y = -2 + 2 + 72y + -72y Combine like terms: -2 + 2 = 0 2 + 2x + -12xy + -72y = 0 + 72y + -72y 2 + 2x + -12xy + -72y = 72y + -72y Combine like terms: 72y + -72y = 0 2 + 2x + -12xy + -72y = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(1 + x + -6xy + -36y) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(1 + x + -6xy + -36y)' equal to zero and attempt to solve: Simplifying 1 + x + -6xy + -36y = 0 Solving 1 + x + -6xy + -36y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + x + -6xy + -1 + -36y = 0 + -1 Reorder the terms: 1 + -1 + x + -6xy + -36y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x + -6xy + -36y = 0 + -1 x + -6xy + -36y = 0 + -1 Combine like terms: 0 + -1 = -1 x + -6xy + -36y = -1 Add '36y' to each side of the equation. x + -6xy + -36y + 36y = -1 + 36y Combine like terms: -36y + 36y = 0 x + -6xy + 0 = -1 + 36y x + -6xy = -1 + 36y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 9-m/7=5 | | 0.5x-7=11 | | -98-3x=4x+112 | | c+3+5= | | 15x+5x^2=0 | | (3x-6)+(2x)+(x+10)+x=360 | | 5(3x+5)=-16+26 | | 10-2d=20 | | 5n^2+30n-200=0 | | 42x^3+82x^2+20x= | | -33-4x=x+37 | | 220=5x | | -5x-16=36-9x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)=0 | | 9/5x=-18 | | (12y+12)+21y= | | 4x+2(x+22)=74 | | (5a^2x+3ax^2-5x)+(2a^2x+5ax^2+7x)=0 | | -0.5*-7=11 | | 5x-4(4/3)=-7 | | 29--10x=-18x+91 | | 24-6x=2x-40 | | X^2-25x/5x | | 3x-54=33+6x | | x^2+18xy+81y^2= | | 28+j=-8 | | X^3+2x+5=0 | | x-1=3x+14 | | (5+x)(6+x)=72 | | 4.92=.55+.23m | | -9x+20+x^2= | | n^2+4n+2=n^2 |